Pengaruh Pendidikan dan Pengembangan Karir Terhadap Hasil Karyawan Investasi Karyawan Sebagai Variabel Lingkungan (Studi Kasus pada Pegawai Kantor Pusat Organisasi XYZ) - Deffi Haryani (STIA Bengkulu, 2024)
The purpose of this study is to dissect the impact of training and career development on hand performance at the head office of XYZ Company using hand engagement as an intermediating variable. This study usednon-probability slice as the slice system and a impregnated sample conforming of 40 mortal coffers workers who have worked in the company for further than two times. Path analysis using SPSS 26 was used as the data analysis system. The results showed that 1) training affects hand engagement 2) career development affects hand engagement 3) training and career development affect hand engagement contemporaneously 4) training has no effect on hand performance 5) career development has no effect on hand performance 6) Proven training, career development and hand engagement affect hand performance contemporaneously.